Busbar at least partially covered with a thermoplastic polyurethane composition
By covering the busbar with a thermoplastic polyurethane composition, the problems of insufficient insulation, flame retardancy and stability of the busbar cover in the prior art are solved, and efficient electrical insulation, flame retardancy and mechanical stability are achieved.
Patent Information
- Application Number
- CN202280054219.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-03
- Filing Date
- 2022-07-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-07-27
AI Technical Summary
The prior art is difficult to provide busbars with high insulation, flame retardancy, stability and covers adapted to extreme temperature variations in electronic mobile components while avoiding the spread of moisture and dust.
Using a busbar covered at least partially with a thermoplastic polyurethane composition, the composition comprising a thermoplastic polyurethane, a flame retardant and a filler, the cover is ensured to have high insulation capability, flame retardant and stability by adjusting the composition and structure.
The high insulation capacity, flame retardancy and stability of the busbar are achieved, and can maintain performance under extreme temperature changes, avoid the spread of moisture and dust, and adapt to the requirements of mechanical fastening and vibration.
Smart Images

Figure BDA0004695290760000131 
Figure BDA0004695290760000171 
Figure BDA0004695290760000181
Abstract
Description
[0001] The present invention relates to an overmolded solid metal conductor, also called a busbar, which is at least partially covered with a thermoplastic polyurethane composition.
[0002] The busbars are usually uninsulated, self-supporting and are located at a sufficient distance from each other to ensure electrical insulation.
[0003] Although busbars are usually uninsulated, in electronic mobile assemblies personnel must be protected from contact with voltage-carrying components. Therefore, different methods of how to cover the busbars are tested, as mentioned, for example, in US 2018 / 334116A1 or US5579217A1.
[0004] Flame-retardant thermoplastic polyurethanes, which are primarily used in cables, are known, see for example EP 3 110 882 A1 or EP 0 617 079 A2.
[0005] The requirement is a high insulating capacity to minimize the space between the multiple busbars. The cover should avoid the spread of moisture and dust between the cover and the busbars and should be flame retardant. At the same time, the cover is required to be stable enough to allow the busbars to be mechanically fastened to another device, and the stability will continue without cracking or shrinking even under extreme temperature changes, such as from freezing temperatures in winter to temperatures of well over 100 degrees and higher that immediately occur when high power is applied to the busbars. Moreover, under these stress conditions, the properties of the polymer should not change, and the extension of the polymer should not exceed the extension of the electronic conductor to avoid corrosion between the two materials. At the same time, the cover should meet additional requirements such as damping and decoupling of vibrations.
[0006] Surprisingly, a busbar at least partially covered with a thermoplastic polyurethane composition according to claim 1 meets these requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figures 1 to 3 A busbar (1) used for testing in an embodiment is shown.
[0008] Figure 1 A 3D top view of a busbar (1) is shown with a copper conductor coated with a lead-tin alloy, partially jacketed with a composition (8) according to the invention. The conductor (3) has two ends for connection with holes (4). The jacket of the composition (8) has two circular notches (5) and one rectangular notch on the top (6) down to the conductor (3). The busbar comprises two crossbars (9) with cylindrical mounting bolts (2) comprising holes (7).
[0009] Figure 2 The conductors are shown from the top, Figure 3The conductor is shown from the side. Both figures give the measurements in mm. DETAILED DESCRIPTION
[0010] The first aspect and embodiment 1 of the present invention is a busbar at least partially covered with a composition comprising a thermoplastic polyurethane, a flame retardant and a filler, wherein the thermoplastic polyurethane is the reaction product of a diisocyanate, a polyol (preferably a polyol diol) and a chain extender.
[0011] A busbar is a metal strip or rod, usually within an enclosure, used for localized high current power distribution. The main function of a busbar is to conduct electrical energy safely and without short circuits, preferably between power storage, motors and charging components.
[0012] The advantages of using busbars instead of power cables are avoiding tangled cables, easy installation, minimizing material usage, reducing weight and reducing inductance. A huge advantage of using thermoplastic polyurethane to cover the busbars is that they are less likely to break at the weld line. The weld line refers to the meeting point of two furnaces, which occurs when filling a complex injection mold (such as for busbars). Thermoplastic polyurethane has also shown to be less likely to crack at a wide range of temperatures below 0 degrees Celsius.
[0013] The term composition means that the composition contains not only thermoplastic polyurethane but may also contain other polymers as well as additives and / or auxiliaries. In a preferred embodiment, the composition contains thermoplastic polyurethane as described below without any other polymers.
[0014] Preferably, the thermoplastic polyurethane is prepared by reacting a diisocyanate with a polyol and, if necessary, a chain extender in the presence of a catalyst and / or auxiliaries and / or additives, the polyol preferably having two hydroxyl groups reactive toward isocyanate and preferably having a molecular weight of 0.5×10 3 g / mol to 10×10 3 g / mol, the chain extender preferably has a number average molecular weight of 0.05×10 3 g / mol to 0.499×10 3 Molecular weight in g / mol.
[0015] The components diisocyanate, polyol and chain extender are also treated individually or together as structural components. The structural components including catalysts and / or auxiliaries and / or additives are also referred to as input materials.
[0016] To adjust the hardness and melt index of thermoplastic polyurethanes (TPUs), the molar ratios of the structural components and the amounts of chain extenders and, if used, water can be varied, whereby hardness and melt viscosity increase with increasing chain extender content while melt flow index decreases.
[0017] In a preferred embodiment, the Shore hardness of the composition is from 65 Shore D to 100 Shore D, preferably measured according to DIN ISO 7619-1:2016, more preferably from 65 Shore D to 85 Shore D. Preferably, the thermoplastic polyurethane contained in the composition has a Shore hardness of from 75 Shore A to 85 Shore D, preferably measured according to DIN ISO 7619-1, 2016, preferably from 95 Shore A to 75 Shore D, more preferably from 60 Shore D to 70 Shore D.
[0018] To prepare the thermoplastic polyurethane, the structural components diisocyanate, polyol and chain extender are reacted in an embodiment preferably in the presence of a catalyst and optional auxiliaries and / or additives in amounts such that the equivalent ratio of the NCO groups of the diisocyanate to the sum of the hydroxyl groups of the polyol and the chain extender is 0.95 to 1.10:1, preferably 0.98 to 1.08:1 and in particular about 1.0 to 1.05:1.
[0019] The thermoplastic polyurethane in the particles from the composition preferably has a particle size between 0.03×10 6 g / mol and 1.5×10 6 g / mol, preferably between 0.04×10 6 g / mol and 1.2×10 6 g / mol, more preferably between 0.05×10 6 g / mol and 0.08×10 6 The thermoplastic polyurethane in the busbar preferably has a weight average molecular weight between 0.03×10 6 g / mol and 1.2×10 6 g / mol, preferably between 0.04×10 6 g / mol and 1.2×10 6 g / mol, more preferably between 0.04×10 6 g / mol and 0.07×10 6 The weight average molecular weight (Mw) is preferably measured according to DIN 55672-2 2016-03.
[0020] In the context of the present invention, molecular weight refers to the number-average molecular weight (Mn), if not indicated differently, and is determined by gel permeation chromatography, preferably in accordance with DIN 55672-1 2016-03.
[0021] Isocyanate
[0022] The diisocyanate is preferably selected from the group consisting of aliphatic, alicyclic, araliphatic and aromatic isocyanates, or a mixture thereof. The isocyanate is more preferably selected from the group comprising trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, heptamethylene diisocyanate and / or octamethylene diisocyanate, 2-methyl-pentamethylene-1,5-diisocyanate, 2-ethyl-butylene-1,4-diisocyanate, 1,5-pentamethylene diisocyanate (PDI), 1,4-butylene diisocyanate, 1-isocyanato-3,3,5-trimethylolpropane. -5-isocyanatomethyl-cyclohexane (isophorone diisocyanate, IPDI), 1,4-bis(isocyanatomethyl)cyclohexane and / or 1,3-bis(isocyanatomethyl)cyclohexane (HXDI), 2,4-p-phenylene diisocyanate (PPDI), 2,4-tetramethylene xylene diisocyanate (TMXDI), 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate and 2,2'-dicyclohexylmethane diisocyanate (H12 MDI), 1,6-hexamethylene diisocyanate (HDI), 1,4-cyclohexane diisocyanate, 1-methyl-2,4-cyclohexane diisocyanate and / or 1-methyl-2,6-cyclohexane diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate and / or 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), 2,4-toluene diisocyanate and / or 2,6-toluene diisocyanate (TDI), 3,3'-dimethyl-diphenyl diisocyanate, 1,2-diphenylethane diisocyanate and / or phenylene diisocyanate, or a mixture thereof.
[0023] When stability to electromagnetic waves, such as light, is important, aliphatic isocyanates are preferred, whereas when high mechanical strength of the thermoplastic polyurethane is required, aromatic polyisocyanates are preferred.Another advantage of aliphatic isocyanates is that they can be produced on a bio-based basis.
[0024] Very preferred aromatic isocyanates are 2,2′-diphenylmethane diisocyanate, 2,4′-diphenylmethane diisocyanate and / or 4,4′-diphenylmethane diisocyanate (MDI), particular preference being given to 4,4′-diphenylmethane diisocyanate.
[0025] A very preferred aliphatic isocyanate is 1,5-pentamethylene diisocyanate. This has the additional advantage that it can be produced on a biological basis.
[0026] Polyols
[0027] The polyol has a statistical average of at least 1.8 and at most 3.0 Zerewitinoff active hydrogen atoms. This value is also referred to as the functionality of the isocyanate-reactive compound (b) and represents the amount of isocyanate-reactive groups in one molecule calculated theoretically from a certain amount of substance. The functionality is preferably between 1.8 and 2.6, further preferably between 1.9 and 2.2, and particularly preferably 2. The isocyanate-reactive compound (b) preferably has a molecular weight between 0.500 g / mol and 8×10 3 g / mol, preferably between 0.7×10 3 g / mol and 6.0×10 3 g / mol, especially between 0.8×10 3 g / mol and 4.0×10 3 Those between 0.1 and 0.1 g / mol.
[0028] The polyol is preferably substantially linear, more preferably linear, and is a single polyol or a mixture of different species, in which case the mixture meets the above requirements.
[0029] These long-chain compounds are used in a content of 1 mol % equivalent to 80 mol % equivalent based on the isocyanate group content of the polyisocyanate.
[0030] Polyols have hydroxyl groups as reactive groups with isocyanates. Polyols are also called polyhydroxy polyols. Polyol (b) is preferably selected from the group consisting of polyesterols, polyetherols or polycarbonate diols, or a mixture thereof, more preferably a polyether polyol.
[0031] In a preferred embodiment 2 including all of the features of embodiment 1 or one of its preferred embodiments, the polyol is a diol.
[0032] In a preferred embodiment 3 comprising all the features of one of the preceding embodiments or one of its preferred embodiments, the polyol is a polyether polyol, preferably a polyether diol.
[0033] In a preferred embodiment 4 including all the features of one of the preceding embodiments or one of its preferred embodiments, the number average molecular weight of the polyether polyol is between 0.6×10 3 g / Mol and 3×10 3 g / Mol, more preferably between 0.8×10 3 g / Mol and 2.5×10 3 g / Mol, more preferably between 1.3×10 3 g / Mol and 1.8×10 3g / Mol, more preferably 1.4×10 3 g / Mol or 1.7×10 3 g / Mol, more preferably the polyether polyol is polytetrahydrofuran (PTHF).
[0034] In a preferred embodiment 5 including all the features of one of the preceding embodiments or one of its preferred embodiments, the number average molecular weight of the polytetrahydrofuran is between 0.6×10 3 g / Mol and 3×10 3 g / Mol, more preferably between 0.8×10 3 g / Mol and 2.5×10 3 g / Mol, more preferably between 1.3×10 3 g / Mol and 1.8×10 3 g / Mol, more preferably 1.4×10 3 g / Mol or 1.7×10 3 g / Mol.
[0035] Polyether polyols
[0036] In a preferred embodiment 6 including all the features of one of the preceding embodiments or one of its preferred embodiments, the polyether polyol comprises a polyether diol, further preferably based on ethylene oxide, propylene oxide, tetrahydrofuran, butylene oxide or a mixture thereof. The most preferred polyether comprises polytetrahydrofuran, more preferably polytetrahydrofuran. .
[0037] The number-average molecular weight Mn in the context of the present invention is preferably determined in accordance with DIN 55672-1.
[0038] Preferred polyether polyols include polytetramethylene ether glycol (also known as PTMEG or PTHF), polypropylene oxide glycol and polybutylene oxide glycol. Particularly preferred is PTMEG or α-hydrogen-ω-hydroxy poly(oxytetramethylene) glycol. They are available under the trade name Commercially available.
[0039] Polyether polyols have the advantage that they are more stable to hydrolysis and therefore will be used in applications requiring this.
[0040] Chain Extender
[0041] According to the present invention, a chain extender is used in the synthesis of thermoplastic polyurethane. In a preferred embodiment 7 including all the features of one of the preceding embodiments or one of its preferred embodiments, the chain extender is preferably a molecular weight of 0.05×10 3 g / mol to 0.499×10 3g / mol of aliphatic, araliphatic, aromatic and / or cycloaliphatic compounds or mixtures thereof, preferably having 2 groups reactive toward isocyanates, also referred to as functional groups. The chain extender is a single chain extender or a mixture of at least two chain extenders.
[0042] The chain extender is preferably a difunctional compound, preferred examples being diamines or alkanediols having 2 to 10 carbon atoms in the alkylene radical, or mixtures thereof.
[0043] In a preferred embodiment 8 including all features of one of the preceding embodiments or one of its preferred embodiments, the chain extender is selected from the group consisting of 1,2-ethanediol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol of dialkylene glycol, dipropylene glycol of trialkylene glycol, dipropylene glycol of tetraalkylene glycol, dipropylene glycol of pentaalkylene glycol, dipropylene glycol of hexaalkylene glycol, dipropylene glycol of heptaalkylene glycol, dipropylene glycol of octaalkylene glycol, dipropylene glycol of nonaalkylene glycol and / or dipropylene glycol of decanediol, 1,4-cyclohexanediol, 1,4-dimethanol cyclohexane, neopentyl glycol and hydroquinone bis(β-hydroxyethyl) ether (HQEE), or a mixture thereof.
[0044] More preferably, the chain extender is selected from the group consisting of 1,2-ethanediol, 1,3-propylene glycol, 1,4-butanediol and 1,6-hexanediol, dialkylene glycol, trialkylene glycol, tetraalkylene glycol, pentaalkylene glycol, hexaalkylene glycol, heptaalkylene glycol, octaalkylene glycol, nonaalkylene glycol and / or decaalkylene glycol, preferably the corresponding oligo- and / or polypropylene glycols, or mixtures thereof.
[0045] In a preferred embodiment 9 comprising all the features of one of the preceding embodiments or one of its preferred embodiments, the chain extender preferably comprises 1,3-propylene glycol, 1,4-butanediol or 1,6-hexanediol or a mixture thereof.
[0046] A preferred mixture of chain extenders is 1,4-butanediol and 1,6-hexanediol or 1,3-propylene glycol, wherein the mole % of 1,4-butanediol is preferably between 80 and 98 mole % referring to the total amount of chain extenders as 100 mole %.
[0047] Another preferred chain extender mixture is 1,3-propylene glycol and 1,6-hexanediol or 1,4-butanediol, wherein the mole % of 1,3-propylene glycol is preferably between 80 and 98 mole % referring to the total amount of chain extenders as 100 mole %.
[0048] In a preferred embodiment 10 according to any one of the preceding embodiments or one of its preferred embodiments, the chain extender preferably comprises 1,4-butanediol.
[0049] catalyst
[0050] In a preferred embodiment 11 according to any of the preceding embodiments or one of its preferred embodiments, a catalyst is used in the synthesis of the thermoplastic polyurethane. Preferred are catalysts that promote the reaction between the NCO groups of the isocyanate (a) and the hydroxyl groups of the isocyanate-reactive compound (also referred to as polyol in the preferred embodiments) and the chain extender. In a preferred embodiment, the catalyst is selected from the group consisting of tertiary amines and organometallic compounds or mixtures thereof.
[0051] Preferred tertiary amines are selected from the group consisting of triethylamine, dimethylcyclohexylamine, N-methylmorpholine, N,N'-dimethylpiperazine, 2-(dimethylaminoethoxy)ethanol, diazabicyclo[2.2.octane] or mixtures thereof.
[0052] Preferred organometallic compounds are selected from the group consisting of titanates, iron compounds, tin compounds and bismuth salts, or mixtures thereof. Preferred iron compounds are iron (III) acetylacetonate. Preferred tin compounds are selected from the group consisting of tin diacetate, tin dioctoate, tin dilaurate and dialkyltin salts of aliphatic carboxylic acids, preferably tin dioctoate, or mixtures thereof. Preferred titanates are tetrabutyl orthotitanate. In preferred bismuth salts, bismuth is present in oxidation state 2 or 3, particularly 3, preferably salts of carboxylic acids, preferably carboxylic acids having 6 to 14 carbon atoms, particularly preferably 8 to 12 carbon atoms. Very preferred bismuth salts are bismuth (III) neodecanoate, bismuth 2-ethylhexanoate or bismuth octoate, or mixtures thereof.
[0053] The catalyst is preferably used in an amount of 0.0001 to 0.1 parts by weight per 100 parts by weight of polyol.Preferred is the use of a tin catalyst, especially tin dioctoate.
[0054] A very preferred catalyst is SDO (tin(II) 2-ethylhexanoate), preferably used in an amount of 0.35 to 0.4 parts by weight, referring to the composition.
[0055] Polyamide
[0056] In a preferred embodiment 12 of the busbar according to one of the preceding embodiments or one of its preferred embodiments, the composition comprises a polyamide or a copolyamide.
[0057] Preferred polyamides or copolyamides are derived from diamines and dicarboxylic acids or from aminocarboxylic acids or from corresponding lactams. Preferred polyamides have a melting point below 230° C. Examples of preferred polyamides are polyamide 5, polyamide 10, polyamide 12, polyamide 11. Other preferred examples are amorphous polyamides, preferably amorphous polyamides which are the reaction product of 15% to 84% by weight of at least one lactam and 16% to 85% by weight of a mixture of monomers (M) comprising monomer (B) and 16% to 85% by weight of a mixture (M) of monomers comprising two monomers B1 and B2, wherein monomer B1 is at least one dimer acid (B1) having 32 to 40 carbon atoms and monomer B2 is at least one diamine having 4 to 12 carbon atoms, and the weight percentages of component (A) and component (B) are each based on the sum of the weight percentages of component (A) and component (B).
[0058] The most preferred amorphous polyamides are polyamide 6 / 6, polyamide 36.
[0059] The lactam is a single lactam or a mixture of at least two lactams, preferably one lactam.Preferred lactams have 4 to 12 carbon atoms, a very preferred lactam is ε-caprolactam.
[0060] Other preferred copolymers are block copolymers of the abovementioned polyamides with polyolefins, with olefin copolymers, with ionomers or with chemically bonded or grafted elastomers; or with polyethers, for example with polyethylene glycol, polypropylene glycol or polytetramethylene glycol, or mixtures thereof. Other preferred examples are EPDM- or ABS-modified polyamides or copolyamides; and polyamides condensed during processing ("IM polyamide systems").
[0061] In a preferred embodiment 13 according to one of the preceding embodiments or one of its preferred embodiments, the weight ratio of the thermoplastic polyurethane and the polyamide or copolyamide in the composition is 1:100 to 100:1, preferably 90:10, 80:20, 70:30 or 60:40, or any other ratio in between.
[0062] Additives
[0063] In a preferred embodiment 14 according to one of the preceding embodiments or one of its preferred embodiments, an auxiliary or additive is added to the structural component. In other words, the additive is contained in the composition. Preferred examples of auxiliary agents include surfactants, fillers, flame retardants, nucleating agents, oxidation stabilizers, lubricants and demoulding aids, dyes, antistatic agents and pigments (if necessary), stabilizers (preferably resistant to hydrolysis, light, heat or discoloration), inorganic fillers and / or organic fillers, reinforcing agents and / or plasticizers.
[0064] Stabilizers in the sense of the present invention are additives which protect plastics or plastic compositions from harmful environmental influences. Preferred examples are primary and secondary antioxidants, hindered phenols, hindered amine light stabilizers, UV absorbers, hydrolysis inhibitors, quenchers and flame retardants. Examples of commercially available stabilizers are given in Plastics Additives Handbook, 5th edition, H. Zweifel, ed., Hanser Publishers, Munich, 2001 ([1]), p. 98-S136.
[0065] Preferably, the number average molecular weight of the ultraviolet absorber is greater than 0.3×10 3 g / Mol, especially greater than 0.39×10 3 g / Mol. In addition, the preferred ultraviolet absorber has a 3 Molecular weight in g / Mol.
[0066] The UV absorber is preferably selected from the group consisting of cinnamate, oxalanilide, benzophenone and benzotriazole, or a mixture thereof, and particularly suitable as the UV absorber is benzotriazole. Examples of particularly suitable UV absorbers are 213. 234. 312, 571, 384 and 82.
[0067] Preferably, the ultraviolet absorber is added in an amount of 0.01 to 5 wt %, preferably 0.1 to 2.0 wt %, particularly 0.2 to 0.5 wt %, based on the total weight of the composition.
[0068] Usually, UV stabilization based on antioxidants and UV absorbers as described above is not sufficient to ensure good stability of the composition against the harmful effects of UV rays. In this case, hindered amine light stabilizers (HALS) are added to the composition in addition to antioxidants and / or UV absorbers, or as a single stabilizer.
[0069] Examples of commercially available HALS stabilizers can be found in Plastics Additive Handbook, 5th edition, H. Zweifel, Hanser Publishers, Munich, 2001, pp. 123-136.
[0070] A particularly preferred hindered amine light stabilizer is bis-(1,2,2,6,6-pentamethylpiperidinyl) sebacate ( 765,Ciba AG) and the condensation product of 1-hydroxyethyl-2,2,6,6-tetramethyl-4-hydroxypiperidine and succinic acid ( 622). In particular, if the titanium content of the end product is less than 150 ppm, preferably less than 50 ppm, in particular less than 10 ppm, based on the components used, the condensation product of 1-hydroxyethyl-2,2,6,6-tetramethyl-4-hydroxypiperidine and succinic acid ( 622).
[0071] The HALS compounds are preferably used in a concentration of 0.01 to 5% by weight, particularly preferably 0.1 to 1% by weight and in particular 0.15 to 0.3% by weight, based on the total weight of the composition.
[0072] Particularly preferred UV stabilizers contain mixtures of phenolic stabilizers, benzotriazoles and HALS compounds in the preferred amounts described above.
[0073] Further information on the abovementioned auxiliaries and additives can be found in the technical literature, for example in Plastics Additives Handbook, 5th edition, H. Zweifel, ed., Hanser Publishers, Munich, 2001.
[0074] e-modulus
[0075] In a preferred embodiment 15 comprising all the features of one of the preceding embodiments or one of its preferred embodiments, the e-modulus of the composition measured according to DIN EN ISO 527 is between 0.05×10 3 MPa and 15×10 3 MPa, preferably between 0.1×10 3 MPa and 10×10 3 MPa, preferably between 0.3×10 3 MPa and 8×10 3 MPa, more preferably between 1×10 3 MPa and 5×10 3 MPa, and even more preferably between 2×10 3 MPa and 3×10 3 Between MPa.
[0076] In a preferred embodiment 16 comprising all the features of one of the preceding embodiments or one of its preferred embodiments, the composition has a Shore hardness between 65D and 100D, more preferably between 65D and 85D. The Shore D hardness is preferably measured according to DIN ISO 7619-1, 2016.
[0077] filler :
[0078] The composition also comprises a filler. The chemical nature and shape of the filler may vary within a wide range if it is sufficiently compatible with the thermoplastic polyurethane.
[0079] Preferred fillers are, for example, glass fibers, glass beads, glass microspheres, carbon fibers, aramid fibers, potassium titanate fibers, liquid crystal polymer fibers, organic fiber fillers or inorganic reinforcing materials. Preferred organic fiber fillers are, for example, cellulose fibers, hemp fibers, sisal or kenaf. Preferred inorganic reinforcing materials are, for example, ceramic fillers or mineral fillers. Preferred ceramic fillers are aluminum and boron nitride. Preferred mineral fillers are asbestos, talc, wollastonite, microvit, silicates, chalk, calcined kaolin, mica and quartz powder, or mixtures thereof.
[0080] In the context of the present invention, fibrous fillers are preferred. The fibers preferably have a diameter of 3 μm to 30 μm, preferably 6 μm to 20 μm, and particularly preferably 8 μm to 15 μm. The fiber length in the compound is preferably 0.02 mm to 1 mm, preferably 0.18 mm to 0.5 mm, and particularly preferably 0.2 mm to 0.4 mm.
[0081] For better compatibility with thermoplastic polyurethane, the fiber filler is preferably surface pretreated with a silane compound.
[0082] Inorganic fiber fillers are preferred. When inorganic fiber fillers are used, better reinforcing effects and higher heat resistance are found.
[0083] Particularly preferred inorganic fillers of the present invention are glass fibers, glass beads or glass microspheres. In another preferred embodiment 17 including all the features of one of the preceding embodiments or one of its preferred embodiments, the filler comprises glass, preferably glass fibers, glass beads or glass microspheres, more preferably glass fibers. The glass is preferably coated. If the glass is a fiber, the thickness of the fiber is preferably 3 μm to 30 μm, in particular 8 μm to 15 μm, and the maximum value of the fiber length distribution is in the range of 0.03 mm to about 15 mm, in particular 1 mm to 10 mm.
[0084] By injection molding, the fibers are given a preferred orientation in the composition, also called flow direction.
[0085] The diameter of the glass beads can vary within a wide range. Suitable and preferred are, for example, beads having an average diameter in the range of 5 μm to 100 μm, preferably in the range of 10 μm to 75 μm, more preferably in the range of 20 μm to 50 μm, more preferably in the range of 20 μm to 40 μm.
[0086] The diameter of the hollow glass microspheres can vary within a wide range. Suitable and preferred are, for example, microspheres with an average diameter in the range of 5 μm to 100 μm, preferably in the range of 10 μm to 75 μm, more preferably in the range of 20 μm to 50 μm, for example in the range of 20 μm to 40 μm.
[0087] Therefore, according to another embodiment 18 according to one of the preceding embodiments or one of its preferred embodiments, the present invention also relates to a busbar with a composition as disclosed above, wherein the microspheres have an average diameter in the range of 5 μm to 100 μm.
[0088] According to the invention, the composition comprises one or more fillers.
[0089] In a preferred embodiment 19 according to one of the preceding embodiments or one of its preferred embodiments, the proportion of filler in the composition is preferably in the range of 5% to 40% by weight, preferably 10% to 30% by weight, more preferably 10% to 20% by weight, more preferably 12% to 18% by weight, based on the weight of the total composition, 100% by weight, preferably 30% to 55% by weight.
[0090] Flame retardants
[0091] The composition of the present invention also comprises at least one flame retardant.
[0092] In a preferred embodiment 20 including all the features of one of the preceding embodiments or one of its preferred embodiments, the filler and flame retardant account for 10 to 60 wt %, preferably 30 to 55 wt % of the composition (being 100 wt %).
[0093] In a preferred embodiment 21 comprising all the features of one of the preceding embodiments or one of its preferred embodiments, referring to the entire composition (being 100 wt%), the composition comprises 3 wt% to 35 wt%, preferably 20 wt% to 35 wt%, and in a preferred embodiment 22 wt% to 28 wt% of flame retardant.
[0094] In a preferred embodiment 22 according to one of the preceding embodiments or one of its preferred embodiments, the flame retardant is halogen-free.
[0095] In another preferred embodiment 23 according to one of the preceding embodiments or one of its preferred embodiments, the flame retardant comprises nitrogen or phosphorus, or a mixture thereof.
[0096] A preferred nitrogen-containing flame retardant is a nitrogen-based compound selected from the group consisting of benzoguanamine, tris(hydroxyethyl)isocyanurate, isocyanurate, allantoin, glycoluril, melamine, melamine cyanurate, melamine polyphosphate, di-melamine phosphate, melamine pyrophosphate, melamine borate, ammonium polyphosphate, melamine ammonium polyphosphate, melamine ammonium pyrophosphate, melamine condensation products selected from the group consisting of melem, melam, melon and higher condensation compounds and other reaction products of melamine with phosphoric acid, melamine derivatives or mixtures thereof.
[0097] More preferably and in an embodiment 24 according to one of the preceding embodiments or one of its preferred embodiments, the flame retardant is chosen from the group consisting of melamine, melamine cyanurate, melamine polyphosphate, di-melamine phosphate, melamine pyrophosphate, melamine borate, ammonium polyphosphate, melamine ammonium polyphosphate, ammonium pyrophosphate and melamine derivatives, or a mixture thereof.
[0098] In another preferred embodiment 25 according to any one of the preceding embodiments or one of its preferred embodiments, the composition comprises a flame retardant selected from the group consisting of melamine, melamine cyanurate, melamine borate, melamine polyphosphate and melamine derivatives, or a mixture thereof. In a very preferred embodiment, the flame retardant (B) is melamine cyanurate. Melamine cyanurate is also known as 1,3,5-triazine-2,4,6 (1H, 3H, 5H) -trione.
[0099] In a preferred embodiment 26 according to any one of the preceding embodiments or one of its preferred embodiments, the composition comprises ammonium polyphosphate as a flame retardant. Preferred flame retardants of this type are ammonium orthophosphate, preferably NH4H2PO4, (NH4)2HPO4 or mixtures thereof; ammonium diphosphate, preferably NH4H3P2O7, (NH4)2H2P2O7, (NH4)3HP2O7, (NH4)4P2O7, or mixtures thereof, ammonium polyphosphate, in particular but not limited to those found in J.Am.Chem.Soc.91,62 (1969). The ammonium phosphate component may or may not be coated. Suitable coated ammonium polyphosphates are described, for example, in US 4,347,334, US 4,467,056, US 4,514,328 and US 4,639,331.
[0100] In a preferred embodiment 27 according to any of the preceding embodiments or one of its preferred embodiments, the flame retardant is an inorganic flame retardant and is preferably selected from the group consisting of magnesium oxide, magnesium hydroxide, silicon oxide, aluminum hydroxide and aluminum oxide, or a mixture thereof.
[0101] In a preferred embodiment 28 according to any one of the preceding embodiments or one of its preferred embodiments, the flame retardant is a phosphorus-containing flame retardant. The phosphorus-containing flame retardant is preferably liquid at 21°C.
[0102] Preference is given to derivatives of phosphoric acid, phosphonic acid or phosphinic acid, or mixtures of two or more of these derivatives.
[0103] It is preferred that the derivatives of phosphoric acid, phosphonic acid or phosphinic acid include salts with organic or inorganic cations or include organic esters. In a preferred embodiment, the organic ester includes an alkyl ester, and in another preferred embodiment, it includes an aryl ester. It is particularly preferred that all hydroxyl groups of the corresponding phosphorus acid have been esterified.
[0104] Preference is given to organic phosphates, in particular triesters of phosphoric acid, more preferably trialkyl phosphates. Other preferred embodiments are triaryl phosphates, particularly preferred is triphenyl phosphate.
[0105] In another embodiment, the phosphate ester has the general formula (I)
[0106]
[0107] wherein R represents a substituted alkyl, cycloalkyl or phenyl group, and n is a real number in the range of ≥1 to ≤15.
[0108] If R in the general formula (I) is an alkyl moiety, the alkyl moieties preferably used are those having 1 to 8 carbon atoms. As a preferred example of a cycloalkyl group, a cyclohexyl moiety can be mentioned. Preferably, a phosphoric acid ester of the general formula (I) is used, wherein R represents a phenyl group or an alkyl-substituted phenyl group. Preferably, n is 1, or in the range of ≥3 to ≤6. Very preferred phosphoric acid esters of the general formula (I) are bis(diphenyl)1,3-phenylene phosphate, bis(xylyl)1,3-phenylene phosphate and corresponding oligomeric products, preferably with an average degree of oligomerization of n in the range of ≥3 to ≤6.
[0109] A highly preferred phosphate is resorcinol, more preferably resorcinol bis(diphenyl phosphate) (RDP). The RDP is preferably present in an oligomer.
[0110] In a preferred embodiment 29 according to one of the preceding embodiments or one of its preferred embodiments, the phosphorus-containing flame retardant comprises bisphenol A bis(diphenyl phosphate) (BDP), diphenylcresyl phosphate (DPC), or a mixture thereof. BPD is usually in the form of an oligomer.
[0111] Organic phosphates include salts with organic or inorganic cations or esters of phosphonic acids. Preferred esters of phosphonic acids are diesters of alkyl or phenylphosphinic acids.
[0112] Phosphinates
[0113] Other preferred phosphorus-containing flame retardants are phosphinates having the general formula R1R2(P=O)OR3, wherein the R3 moiety is an organic group, and R1 and R2 are organic groups or hydrogen.
[0114] In a preferred embodiment, the moiety R1, the moiety R2 and the moiety R3 are identical, in another preferred embodiment, R1, R2 and R3 are different from each other.
[0115] R3 is preferably an aliphatic group or an aromatic group, and preferably has 1 to 20 carbon atoms, more preferably 1 to 10. In a preferred embodiment, the aliphatic group has 1 to 3 carbon atoms, more preferably R3 is an ethyl radical or a methyl radical.
[0116] The moiety R1, the moiety R2 preferably has 1 to 20 carbon atoms, more preferably 1 to 10 carbon atoms, preferably at least one of the moiety R1, the moiety R2 or the moiety R3 is aliphatic, and more preferably the aliphatic group has 1 to 3 carbon atoms. More preferably, the moiety R1, the moiety R2 and the moiety R3 are all aliphatic groups, as outlined above.
[0117] In a preferred embodiment, R1 and R2 are ethyl radicals, and more preferably in this embodiment, R3 is also ethyl radicals or methyl radicals. In a preferred embodiment, R1, R2 and R3 are ethyl radicals or methyl radicals simultaneously. In another preferred embodiment, R1 and R2 are hydrogen atoms.
[0118] Phosphinates
[0119] Also preferred are metals (M + ) phosphinate, which is a general formula M + [R1R2(P=O)O] - The metal of the phosphinate (M +) salt. The radical R1 and the radical R2 are hydrogen, aliphatic or aromatic and preferably have 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, more preferably 1 to 3 carbon atoms. It is preferred that at least one part is aliphatic, and more preferably both parts are aliphatic, and it is very particularly preferred that R1 and R2 are methyl radicals or ethyl radicals, most preferably ethyl radicals.
[0120] In a preferred embodiment 30 according to one of the preceding embodiments or one of its preferred embodiments, the flame retardant comprises a phosphinate.
[0121] In a preferred embodiment 31 according to one of the preceding embodiments or one of its preferred embodiments, the flame retardant comprises a phosphinate from the group consisting of aluminum phosphinate, calcium phosphinate, titanium phosphinate, zinc phosphinate, or a mixture thereof, more preferably aluminum phosphinate.
[0122] In other preferred embodiments, the R1 or R2 radical is a hydrogen atom and the other radical is an organic radical, with the preferences given above. In another embodiment, the R1 and R2 radicals are hydrogen atoms.
[0123] Preferred phosphinic acid salts are aluminum, calcium, titanium or zinc salts, or mixtures thereof. Aluminum is more preferred.
[0124] More preferably, the metal phosphinate is selected from: zinc diethylphosphinate, aluminum diethylphosphinate, aluminum phosphinate, calcium phosphinate, or a mixture thereof. More preferably, it is aluminum diethylphosphinate or aluminum phosphinate, or a mixture thereof. Most preferably, it is aluminum diethylphosphinate.
[0125] Preferably, the flame retardant is selected from: derivatives of phosphinic acid, salts with organic or inorganic cations or organic esters. Organic esters are derivatives of phosphinic acid in which at least one oxygen atom directly bound to phosphorus is esterified with an organic residue. In a preferred form, the organic ester is an alkyl ester, in another preferred form an aryl ester. All hydroxyl groups of the phosphinic acid are particularly preferably esterified.
[0126] Furthermore, in a preferred embodiment, piperazine pyrophosphate and piperazine pyrophosphate are used as flame retardants.The use of piperazine-based flame retardants is known in principle from the prior art, for example as disclosed in WO 2012 / 174712 A1.
[0127] The flame retardant is used in the composition as a single substance or as a mixture of several substances of the same kind of flame retardant or of different kinds of flame retardants.
[0128] In a preferred embodiment 32 according to one of the preceding embodiments or one of its preferred embodiments, the flame retardant comprises a first phosphorus-containing flame retardant (F1) selected from the group consisting of melamine polyphosphate and another phosphorus-containing flame retardant (F2) selected from the group consisting of derivatives of the phosphinic acid given above as preferred, most preferably aluminum phosphite.
[0129] In a preferred embodiment 33 according to one of the preceding embodiments or one of its preferred embodiments, the flame retardant comprises melamine cyanurate [=(1,3,5-triazine-2,4,6(1H,3H,5H)-trione] and a phosphate ester, more preferably the phosphate ester resorcinol bis(diphenyl phosphate).
[0130] Melamine polyphosphate preferably has a phosphorus content of between 7% and 20% by weight, preferably in the range of 10% to 17% by weight, more preferably in the range of 12% to 14% by weight.
[0131] A further embodiment preferably employs melamine polyphosphate which has a pH value in the range from 3 to 7, more preferably in the range from 3.5 to 6.5, particularly preferably in the range from 4 to 6, determined in each case to ISO 976, in aqueous solution.
[0132] It is preferred that the flame retardant (F2) is selected from the derivatives of phosphinic acid, the preferences being given above.
[0133] Water absorption
[0134] In a preferred embodiment 34, the composition of the busbar according to one of the preceding embodiments or one of its preferred embodiments has a water absorption, measured according to DIN EN ISO 62, method 1, of less than 1% and measured according to DIN EN ISO 62, method 4, of less than 0.5%.
[0135] Glass temperature
[0136] In a preferred embodiment 35, the composition of the busbar according to one of the preceding embodiments or one of its preferred embodiments has a glass temperature T of less than -30°C, preferably less than -40°C, and most preferably less than -50°C. g . Glass temperature T g Preferably measured by dynamic mechanical analysis, deformation frequency 1 Hz, loss modulus (maximum G") [°C] (DIN 53019 DIN EN 3219).
[0137] UL94
[0138] In a preferred embodiment 36, the composition of the busbar according to one of the preceding embodiments or one of its preferred embodiments passes the UL 94V vertical 2mm test (ANSI, UL94 "Tests for Flammability of Plastic Materials for Parts in Devices and Appliances" Sixth Edition, dated March 28, 2013). In a preferred embodiment, the busbar complies with UL24 classification V0, V1, V2, more preferably classification V0 or V1, and particularly preferably classification V0.
[0139] Shrinkage
[0140] In a preferred embodiment 37, the composition of the busbar according to any of the preceding embodiments or one of its preferred embodiments has a shrinkage of less than 0.8%, preferably less than 0.6%, more preferably less than 0.4%, preferably measured according to ISO 294-4.
[0141] CLTE (Coefficient of Linear Thermal Expansion)
[0142] In a preferred embodiment 38 of the composition of the busbar according to any one of the preceding embodiments or one of its preferred embodiments, the CLTE (linear thermal expansion coefficient) of the composition in the longitudinal direction of the fiber is less than 150 10 -6 1 / K, preferably less than 80 10 -6 1 / K, preferably measured according to ISO 11359-2. In a further preferred embodiment 39, the composition of the busbar according to any one of the preceding embodiments or one of its preferred embodiments has a CLTE (if applicable transverse to the fiber direction) of less than 150 10 -6 1 / K, preferably less than 80 10 -6 1 / K is preferably determined according to ISO 11359-2.
[0143] Busbar
[0144] The busbars are usually uninsulated, self-supporting and have a sufficient distance between each other to ensure electrical insulation. The form of the busbar depends on its specific requirements, such as installation space, the number of plugs to be adapted to voltage or current. The material of the busbar conductive part of the busbar is a metal, preferably selected from the group consisting of: aluminum, steel, iron, copper, lead, tin, zinc, or an alloy thereof. An alloy of lead and tin is a preferred covering of a metal, preferably copper.
[0145] In a preferred embodiment 40, the busbar according to any of the preceding embodiments or one of its preferred embodiments complies with the climate change test as outlined in detail in Example 4.
[0146] Method for preparing busbar
[0147] Another aspect and preferred embodiment 41 is the preparation of a busbar according to any one of the preceding embodiments or one of its preferred embodiments. The conductive part of the busbar is placed in a mold. In a preferred embodiment, the device for fixing the busbar is positioned in the mold together with the conductive part. In the next step, the mold is filled with the composition and demolded after the composition is cured. The particles of the composition are preferably dried before being used for injection molding, preferably dried for at least 3 hours, preferably dried at about 90°C.
[0148] use
[0149] Another aspect and embodiment 42 of the present invention is the use of the thermoplastic polyurethane composition as described above for covering a device, preferably an electronic device, more preferably a busbar.
[0150] In a preferred embodiment 43, the corresponding thermoplastic polyurethane composition is in the form of pellets or powder. In a preferred embodiment, the pellets or powder are dense materials. In another preferred embodiment, the pellets are expanded materials, also known as foamed beads or powders.
[0151] experiment
[0152] Example 1: Raw materials
[0153]
[0154]
[0155] Example 2: Preparation of Thermoplastic Polyurethane AF
[0156] Table 1 below shows the formulations of thermoplastic polyurethanes (TPU) A to F, where the weight parts (PW) of the individual starting materials are given. The polyols are placed in a container at 80°C and mixed with the components in a reaction vessel under vigorous agitation according to the amounts given in Table 1. The isocyanate is added to the last component. Once a reaction temperature of 110°C is reached or the foam level exceeds 80% of the volume of the reaction vessel. The reaction mixture is poured onto a hot plate (120°C) to form a block. The block is cured on the plate for 10 min, then tempered at 80°C for 15 h, crushed and extruded into granules.
[0157] Example 3: Preparation of Compositions 1-12
[0158] Compositions 1-12 having a mixture of the ingredients shown in Tables 2 and 3 were prepared in a ZE 40, a twin-screw extruder from Berstorff with a screw length of 35D divided into 10 barrel segments (compounding). Granules were obtained using an underwater granulation unit from Gala. Granules of the thermoplastic polyurethane used were dried at 90° C. for 3 hours before compounding.
[0159] Example 4: Determination of properties
[0160] The mechanical properties of the thermoplastic polyurethanes (TPU) from formulations A to F and compositions 1-12 were determined on injection molded test bodies. The TPU compositions were each dried at 90° C. for 3 hours, then injection molded into test bodies and measured with the following specifications. The properties of the test bodies of the individual materials are summarized in Tables 1, 2 and 3.
[0161]
[0162] Table 1: Properties of thermoplastic polyurethane (TPU) AF
[0163]
[0164]
[0165] The thermoplastic polyurethanes derived from formulations D, E, and F achieve the desired stiffness above 300 MPa.
[0166] All materials had high shrinkage, which was due to the fact that none of the TPUs in Formulations A to F achieved the required flame retardancy.
[0167] Table 2: Properties of compositions 1-6
[0168]
[0169]
[0170] Compositions 4-6 have the required stiffness and flame retardancy and also pass the climate change test. However, compositions 4-6 have a large shrinkage rate.
[0171] Table 3: Properties of Compositions 7-12
[0172]
[0173] In addition to flame retardancy and low shrinkage, all formulations have a sufficiently high elastic modulus
[0174] Furthermore, the formulation according to the present invention comprises a molecule with an average molecular weight of 1.4×10 3 g / mol and 1.7×103 The preparation of the polyTHF mixture with a concentration of 100 g / mol was subjected to the climate change test.
[0175] Example 5: Overmolding of busbars
[0176] To produce the test busbars as outlined in more detail in the figure, the thermoplastic polyurethane (TPU) or the composition was dried at 90° C. for 3 hours. A standard injection molding machine was used. The mold was mounted on a guide rail system. A busbar made of copper with a coating made of a lead / tin alloy was placed in the injection mold. The injection molding of the thermoplastic polyurethane or the composition was carried out using the following parameters:
[0177] Melt temperature [T°]: 220℃ / 230℃
[0178] Cylinder zone (nozzle to funnel) temperature: 230℃ / 220℃ / 210℃ / 200℃
[0179] Mold temperature Wg[T°]: 45°C
[0180] Back pressure: 5 bar to 10 bar
[0181] Circumferential speed: 0.2m / s
[0182] Injection speed: 20mm / s to 30mm / s.
[0183] Injection time: 0.9s to 1.5s
[0184] Switching point: 10mm
[0185] In-mold thermal transfer (Reprint): 80% of switching pressure
[0186] In-mold heat transfer time: 15s for 2mm thick coating
[0187] Residual mass impact: 6mm
[0188] Cooldown time: 15s
Claims
1. A busbar, the busbar being at least partially covered with a composition comprising a thermoplastic polyurethane, a flame retardant and a filler, wherein the thermoplastic polyurethane is a reaction product of a diisocyanate, a polyol and a chain extender; wherein the polyol is a polyether polyol, and the number average molecular weight of the polyether polyol is between 1.3×10 3 g / Mol and 1.8×10 3 Between g / Mol, determined according to DIN 55672-1. The busbar according to claim 1 , wherein the polyol is a polyether diol.
3. The busbar according to claim 1 or 2, wherein the number average molecular weight of the polyether polyol is between 1.4×10 3 g / Mol and 1.7×10 3 Between g / Mol. The busbar according to claim 1 or 2, wherein the polyether polyol is polytetrahydrofuran (PTHF).
5. The busbar according to claim 1 or 2, wherein the e-modulus of the composition measured according to DIN EN ISO 527 is between 0.05×10 3 MPa and 15×10 3 Between MPa. The busbar according to claim 1 , wherein the filler is glass.
7. The busbar according to claim 1 or 2, wherein the flame retardant is halogen-free.
8. The busbar according to claim 1 or 2, wherein the flame retardant comprises nitrogen or phosphorus, or a mixture thereof.
Citation Information
Patent Citations
Self extinguishing thermoplastic polyurethanes and process for their preparation
EP0617079A2
Flame-retardant thermoplastic polyurethane
EP3110882A1
Electrical busbar
US20180334116A1
Particulate agent for impeding the combustibility of combustible substances
US4347334A
Particulate agent for impeding the combustibility of combustible materials
US4467056A